Tithing: Instruction or Instructive? - Parker, David M. (Journal of pentecostal theology, 2012)
After surveying the disparate Old Testament material on tithing, this paper isolated 1 Corinthians 9 as the loudest echo of that practice. It then modelled 1Corinthians 9 and 10 as illustrative rather than regulative in its approach to the former testament. Utilizing the ‘lesser-to-greater’ (qal wāḥômer) argument inherent in 1 Corinthians 9, it developed an implied benchmark of tithing in 1 Corinthians 9 and 1 Tim. 5.17 to argue such as the base upon which NT giving is predicated. Noting the socio-economic disparity of Corinth, in comparison with the ideal distribution by which the Hebrew Scriptures regulated tithes, the paper then invoked the gift of giving from Rom. 12.8 to suggest proportional giving rather than the strict regulation of the Mosaic legislation. Finally, returning to the literary setting of 1 Corinthians 9, any conclusion, at least from the Pauline corpus, was shown to be contextually suggestive, not invariably regulative.